Acoustical Studies on Hydroxypropyl Methylcellulose in Alcohols and Methylene Chloride Mixture - RAJU, K.; RAKKAPPAN, C. (Asian Journal of Chemistry, 2010)
Ultrasonic velocity, viscosity and density for the solutions of hydroxypropyl methyl cellulose (HPMC) in propan-1-ol, butan-1-ol, pentan-1-ol and hexan-1-ol with methylene chloride (1:1) mixtures were measured at 303 K. From the experimental data observed as a function of concentration, various acoustical parameters such as, adiabatic compressibility, internal pressure, intermolecular free length, free volume and solvation number were calculated. The results are interpreted in terms of molecular interactions occurring in the solutions.